Sentiment Analysis and Factors Influencing the Adoption of Islamic Digital Banking among the Millennial Generation in Indonesia - Farida Ayu Avisena Nusantari; Eryco Muhdaliha; Mia Laksmiwati (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This research explores the factors influencing the adoption of Islamic digital banking among millennials in Indonesia. Employing a qualitative approach through a comprehensive literature review, the study analyzes existing research on Islamic digital banking adoption, focusing on academic journals, conference proceedings, and industry reports. The findings reveal that perceived ease of use and usefulness of digital banking services are crucial. Additionally, social influences, such as peer and family recommendations, and personal factors, including demographics and cultural background, significantly impact adoption rates. This research provides valuable insights for Islamic banks in Indonesia to develop targeted strategies for millennial engagement. By understanding these influencing factors, Islamic banks can tailor digital banking services to meet the specific needs and preferences of this demographic, thereby enhancing market penetration and fostering growth within the evolving digital banking landscape.